Target-controlled infusion of remifentanil for conscious sedation during spinal anesthesia - Byun, Sung Hye (The Korean Society of Anesthesiologists, 2011)
BACKGROUND: The aim of this study was to define the optimal target concentration of remifentanil which effectively achieves conscious sedation without significant vital sign changes and side effects during spinal anesthesia. METHODS: Sixty patients underwent spinal anesthesia with 0.5% hyperbaric bupivacaine (8-16 mg), and were infused with a target controlled infusion (TCI) of remifentanil at 1.0 ng/ml (group R10, n = 15), 2.0 ng/ml (group R20, n = 15), 3.0 ng/ml (group R30, n = 15), and 3.5 ng/ml (group R35, n = 15). Observer's assessment of alertness/sedation (OAA/S) scale, the bispectral index (BIS), anxiety levels and infusion rate of remifentanil were monitored during the operation. RESULTS: OAA/S scale was significantly lower in groups R30 (3.96) and R35 (3.34) than groups R10 (4.31) and R20 (4.26). Incidence of intraoperative respiratory depression events, post operative nausea and vomiting were significantly higher in group R35 than the other groups. There were no significant differences in BIS, anxiety level and incidences of recall of the operative procedure among the groups. CONCLUSIONS: We conclude that the TCI of remifentanil at 3.0 ng/ml produces an effective sedation and anti-anxiety effects without significant side effects during spinal anesthesia.